Calculations of Bending and Contact Rigidity of Gear Teeth and Wheel (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article examines the influence of wear loss values in the unit and parts of the wheel-motor unit of the UZTE16M mainline diesel locomotive on the dependence of the contact and bending stiffness of the gear and wheel.